The TINJAUAN HUKUM ISLAM TERHADAP AKAD HYPNOTHERAPY - Nabella Dananier; Yusron Wijaya (Postgraduate State Islamic Institute (IAIN) Metro, 2021)
Islamic law is basically a universal law that can be applied without being constrained by time. The elasticity of Islamic law provides answers to every phenomenon that arises so that Islamic law will always be relevant to be applied anytime and anywhere and there is no doubt that Islamic law is eternal. Lately there are many alternative treatments commonly called hypnotherapy. Hypnotherapy is a method of treatment using hypnotic patterns. Hypnotherapy in its development continues to undergo modifications from its practitioners, because each hypnotherapist has values that make it unique. The review of Islamic law on hypnotherapy contracts aims to find out the truth about the practice of hypnotherapy, especially in the PPT Counseling and Psychotherapy Clinic in Yogyakarta. In this study using qualitative methods with data collection through interviews and documentation. The primary informants in the study were hypnotherapists and clients who had undergone hypnotherapy. The data obtained is then analyzed by relating it to Islamic law. The application of the contract in hypnotherapy at the PPT Counseling and Psychotherapy Clinic in the Yogyakarta area does not violate sharia principles. This is because the contract that occurs in hypnotherapy is fulfilled properly. In addition, there is no element of coercion at all, because the hypnotherapy they undergo requires a voluntary state from the client to facilitate the hypnotherapy process